Will Energy Save FDI Inflows to Turkey from the Cool Down of EU Accession Prospects? : A Case Study of How Geo-political Alliances and Regional Networks Matter - Sánchez-Martín, Miguel Eduardo (Taylor and Francis, 2015)
Turkey has historically struggled to attract foreign investors. This paper discusses how the start of the European Union's accession negotiations in 2005 encompassed a wide set of reforms in several chapters of the acquis communautaire that resulted in higher foreign direct investment (FDI) attraction. However, it seems that the global economic slowdown of 2009 coupled with increasing Euro-skepticism have already started to erode this effect. Only large a volume of foreign investment in the energy sector observed in 2009–13, explained by the energy security strategy of the European Union and the internal liberalization agenda, has prevented the collapse of FDI inflows to Turkey.